Resistance of exotic collections of gerbera (Gerbera jamesonii) against whitefly (Bemisia tabaci) and thrips (Thrips palmi) under polyhouse conditions - Reddy, P. Venkata Rami; Aswath, C (The Indian Journal of Agricultural Sciences, 2008)
An experiment was conducted during 2003-04 to study the resistance of 16 exotic collections of gerbera (Gerbera jamesonii Bolus ex. Hooker F.) against whitefly (Bemisia tabaci Genn.) and thrips (Thripspalmi Karney) under polyhouse conditions at Bangalore. Of the 16 collections screened, 2 varieties ’Eva’, and ’Carocci’ showed combined resistance to both whitefly and thrips while 3 varieties ’Alberino’ ’Dil’, and ’Cassiona’ were highly susceptible to both the pests. Varietal reactions were also studied in relation to flower structure type and colour. It was found that double types were least susceptible (38.26%) to thrips damage compared to single (56.48%) and semi-double types (75.38%). Among flower colours, red colour attracted highiest thrips incidence (77.89%), followed by yellow (59.61%) while pink varieties had significantly less damage (34.37%).